Defining Street Gangs in the 21st Century Fluid, Mobile, and Transnational Networks - Prowse, C.E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
1
Introduction -- The Gangs as a Network -- From Fixed to Mobile, Members to Players -- Criminal Enterprise -- Managing the Problem.
Keywords: Social sciences; Criminology; Social Sciences; Criminology & Criminal Justice